An Interface for Visualizing Applied Interventions Data through Mobile Devices - Scalco, Leonardo Fernandes; Rodrigues, Kamila Rios da Hora; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
Professionals or researchers who, in diverse areas, need to accompany users (e.g., patients or students), and they use approaches that allow to collect daily data from their users. These specialists accompany and carry out collection through the planning and implementation of intervention programs. The objective of this work is to understand how the specialists visualize and analyze data, offering an alternative visualization form, based on the combination of different techniques, that allows the specialists to make use of the structure of the intervention programs to follow the application of these programs. A study was carried out with healthcare professionals and through the analysis of a visualization prototype and graph structures, it was possible to understand how these specialists interpret their data. We also identified requirements for our visualization interface.